Grupo pequeño de personas reunidos al aire libre. (UNED, 2023)
Aparece Carlos Saborío Elizondo, Marcial Prado Quesada, Manuel Murillo Alfaro, se ve la cabeza de Luis Guillermo Carpio Malavassi, Carlos Luis Montero Alfaro, de espalda Pablo Ramírez Mendoza afuera del Edifico B